P429 Patient skeletal muscle area and postoperative clinical recurrence in Crohn's disease: a retrospective study. (30th January 2023) - Inniss, S; Simpson, K; Fragkos, K; Wood, C; Smith, A; Rahman, F
Abstract: Background: Sarcopenia, a reduction in muscle mass and function, is a poorly recognised phenomenon in Crohn's disease (CD) despite occurring in 16%-68% of CD patients [1-5] . It has been linked to both an increased need for surgery and increased risk of postoperative complications. However, the role of sarcopenia in CD and its long-term impact on surgical outcomes are unknown. We aimed to assess the link between sarcopenia and postoperative clinical recurrence. Methods: Retrospective data was collected between 2015 and 2021 from CD patients who had undergone gastrointestinal surgery and a MR or CT scan within 3 months prior to surgery. Follow up data was retrospectively collected for 6 months. MR and CT scans were used to determine skeletal muscle area (SMA) from the cross-sectional L3 vertebrae, which was used to identify patients as sarcopenic or not. Clinical recurrence was defined as a Harvey-Bradshaw Index of 5 or more. Statistical analysis included demographics and inferential analyses. Missing data was attributed to the absence in clinic notes. Results: This single centre study included 64 CD patients [56.3% male, median age of 30.0 (18.0-76.0), 87.7% non-smokers] who had undergone gastrointestinal surgery. Most patients had ileocolonic CD (74.6%, 47/63) and either stricturing (46.9%, 30/64) or penetrating (31.3%, 20/64) disease behaviour, and 23.4% (15/64) had perianal disease. 45.3% (29/64) of patients had had at least one previous surgery. Preoperatively, 20.6% (13/63) of patients were on steroids and 55.6% (35/63) were on combined drug therapy. Patient median SMA was 113.6 (61.8 – 281.7) cm 2 with sarcopenia found in 74.1% (43/58) of patients. SMA was lower in females (females: 92.1±19.3 cm 2 vs males: 137±39.5 cm 2, p<0.001) and patients with a BMI<18.5 kg/m 2 (BMI<18.5 kg/m 2 : 91.8±19.1 cm 2 vs BMI≥18.5 kg /m 2 : 120.3±33.3 cm 2, p=0.004) (figure 1). Postoperative clinical recurrence was observed in 17.8% (8/45) of patients at 6 months. Patients with clinical recurrence had a significantly lower SMA (87.4 ± 18.5 cm 2 ) compared to those without clinical recurrence (120.9 ± 39.2 cm 2 ) (p=0.001) (figure 2). Patients with a lower SMA were 1.1 times more likely to have clinical recurrence at 6 months compared to patients with a higher SMA (OR 1.05 (CI 1.01-1.10)(p=0.022)). Conclusion: Sarcopenia is highly prevalent in preoperative CD patients. Patients with early clinical recurrence had a significantly lower SMA. SMA may be useful in predicting CD patients at risk of early postoperative clinical recurrence. However, more research is needed to confirm study findings.